Plan de mejoramiento integral para el alberge San Juan de Dios ubicado en la ciudad de Quito - Morales López, Jeniffer Ivonn (2015)
The shelter “San Juan de Dios” was created on 9 of December in the year of 1987, in Quito on Tejar Neighborhood, since that moment the shelter helped mother and children and also old people and people with mental illness. Also the shelter helps people from other countries who don’t have food and a home were they can live. In the year of 2000 the shelter got a land of 5000 m that was on the street Tumbez y Bahia de Caraquez on San Diego; thanks to the help of “Agencia Española de Dios” in Spain, this will be opening on March of 2002 and this will recived 300 people. The shelter has become the home of sixty adults who are abandoned whit different health problems, and also 200 people recived bed and food inside the shelter.